Outcome of Dorsal Wrist Ganglion Surgical Excision - Muhammad Bilal, Muhammad Shakeel Basit, Abdul Hannan, Kazi Muhammad Saeed, Adil Kazi, Hassan Abbas Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate the clinical outcome of dorsal wrist ganglion treated with surgical excision. Methodology: It was a cross-sectional study performed at Kazi Hospital Lahore. Non-probability purposive sampling technique was used to enroll 50 patients of dorsal wrist ganglion who responded through a questionnaire / research proforma. Surgical excision was done under local anesthesia as day case. Results: We collected data of 55 patients. The mean age of the patients having dorsal wrist ganglion cyst was 31. Female patients were in a larger proportion than male patients. Right wrist was affected in n= 29 (58 %) of the individuals. At the end of our follow up only 2(45) patients had residual pain. Hypertrophic scar has been reported to be associated with the lower patient satisfaction (p = 0.001). Luckily in our study only two patients (4%) had this problem. Conclusion: This study concluded that the outcomes of surgical excision of dorsal wrist ganglion is effective technique with high patient satisfaction and cost effectiveness. Keywords: Dorsal wrist ganglion, aspiration, surgical excision, outcome, patient satisfaction.